Perser, Meder und Parther im Spiegel der Quellen - Oliver Bräckel (Digital Classics Online)
The following article is another contribution to the use of tag pies in the wide field of Digital Humanities. Wordclouds provide suitable means when summarizing and visualizing data to support the analysis of analytical tasks and examining of bigger collections of text. The specific use in the field of Classics will be illustrated by means of examining the corpus of the TLG (Thesaurus Linguae Graecae) with regard to the specific question about the connection of three ancient nations: Persians, Medes and Parthians. How are these nations described by the ancient authors and where are the differences and similarities between them? Hence it should be obvious which possibilities tag pies offer to help to work on specific scholarly tasks and where the limitations of this method lie.